Responsabilidade dos administradores por danos causados às sociedades anônimas abertas - Barcelos, Brenno Roberto Amorim [UNESP] (2016)
The issue of liability of the company managers gain added importance in times of economic and financial crisis, therefore, highly profitable companies now shows deficit, embittering losses, increasing debts, reducing the dividend distribution. In this scenario, should be analyzed with technical precision the performance of managers in order to realize what is the importance and responsibility in the bad results obtained by the corporation. To this end, necessary look the duties and obligations tha fall on administrator, the legal nature of this responsibility and also the procedural legal instruments to the company disposal injured in order to recover damages possibly caused by it´s officers, in particular, on social responsibility action.